ANALISIS STRATEGI PENGEMBANGAN DESTINASI PARIWISATA HALAL PERKAMPUNGAN BUDAYA BETAWI SETU BABAKAN JAKARTA - Fara Fitra Ramadani (2023)
Halal tourism is a sector of the Islamic Economy that is growing quite rapidly. In 2024, the DKI Jakarta Government is targeting Jakarta to become Indonesia's best halal tourist destination. Therefore, the DKI Jakarta Government has launched several tourist destinations as pilot areas for halal tourism, one of which is PBB Setu Babakan Jakarta. This research uses a descriptive qualitative approach. Using the SWOT analysis method and referring to the halal tourism indicators from the Global Muslim Travel Index 2019 and the Indonesia Muslim Travel Index 2019. The results of the strategy formulation with the SWOT analysis show that the Setu Babakan tourist destination is in quadrant I, which means the strategy needed for this situation is a growth strategy. Then the results of the formulation of the IE matrix show that PBB Setu Babakan is in quadrant IV which means is in a position to grow and build. The strategies needed for this situation are an integration strategy and an intensive strategy. Such as, conducting partnerships and cooperation, product development, infrastructure development, promotion, and marketing.